Risk Stratification by Cardiac Biomarkers following Emergency Gastrointestinal Surgery. (10th October 2011) - Cahill, T. J.; Bowes, P.; Duncan, E.; Drye, E.; Sen, S.; Miller, C.; Reshamwalla, S.; Andrew, C.; Ward, M.; Bakhai, A.
Abstract : Perioperative cardiac complications are a major cause of death following emergency gastrointestinal surgery. Early diagnosis of subclinical myocardial injury and infarction may be improved by screening with cardiac biomarkers. The aim of this study was to assess the predictive value of troponin I (TnI) and B-type natriuretic peptide (BNP) in the early postoperative period after emergency gastrointestinal surgery. We prospectively recruited 48 patients undergoing major emergency surgery for gastrointestinal or colorectal pathology in a single district general hospital. The primary endpoint was mortality at 90 days following surgery. Overall survival was 81.3% (39/48), with 9 postoperative deaths. Elevated TnI (≥0.03 ng mL − 1 ) was the best predictor of mortality, associated with an odds ratio of death by 90 days of 14.3 (95% CI 1.50–337, P = 0.01 ). A postoperative BNP concentration >408.5 pg mL − 1 was associated with an odds ratio of death by 90 days of 13.6 (95% CI 2.03–106, P = 0.002 ). A single measurement of postoperative BNP and TnI is a powerful predictor of short- to medium-term mortality in patients after emergency gastrointestinal surgery. Further work is required to demonstrate that cardiac biomarkers have independent predictive power and that patient outcomes can be improved.